Parents, friends and immigrant youths' academic engagement: A mediation analysis. (13th April 2020) - Smith, Naila A.; Brown, Joshua L.; Tran, Tran; Suárez‐Orozco, Carola
Abstract : Parents and friends can help facilitate the academic engagement of newcomer immigrant youth during the early post‐migration years. Using an accelerated longitudinal design and the integrative risk and resilience framework, we examined how parent home involvement and friendships were directly and indirectly associated with the development of newcomer immigrant youths' academic engagement. We used data from three waves (Years 3–5) of the Longitudinal Immigrant Student Adaptation study where a culturally diverse group of immigrant youth ( N  = 354, ages 10–17, M timeinUS  = 3.98 years, SD  = 1.39) in the United States reported on their perceptions of parent home involvement (educational values and communication) and friendship (educational values and academic support) in Year 3 and on their academic engagement (behavioural and emotional) across 3 years. Findings showed high‐stable behavioural and emotional engagement and direct positive associations between perceptions of parent home involvement and initial levels of behavioural and emotional engagement and between perceptions of friend educational values and initial levels of emotional engagement. Additionally, perceptions of parents' educational values indirectly contributed to initial levels of emotional engagement through positive associations with perceptions of friends' educational values. These findings can inform family–school partnerships and school‐interventions targeting newcomer immigrant youths' engagement.